Evolução geomórfica e modelagem termocinemática 3D da região do planalto de Poços de Caldas (SP/MG) - Doranti-Tiritan, Carolina [UNESP] (2013)
The Sul de Minas plateau region is located in the southeast of Brazil and it is caractherizide mainly by the highest plateaus sustainted by crystalline rocks of Precambrian and Cambro-Ordovician cut by alkaline rocks on the upper Cretaceous. In this region the Poços de Caldas Alkaline Massif (MAPC) is a particular structure that have been studied for a long time. The intrusion age is about 80 to 50Ma that allows defining a time limit to the forming process of the drainage and the relief of the region. Areas as the MAPC are subject to an intense erosion process that lead to a rock cooling, that can be registered by thermochronology techniques that estimate the time the rock pass through the correspondent isotherm of the closing temperature of the method. The surfaces rocks would be exhumated before to reach the closing temperature. Therefore the aim of the work was quantify the main processes that were responsible for the evolution of the landscape by using methods as the low temperature thermochronology, the river morphometric analysis and the 3D thermo modeling, for obtaining data of uplift and erosion rates and to correlate them with the therma gradients of the region. The 3D thermal modeling was obtained usin the PECUBE software (Braun 2003). It is a finite code that solves the heat flow equation. The region as subdivided in tree areas Poços de Caldas (PC); Zona Cristalina do Norte (ZCN) and Morro do Ferro (MF). Data show that the uplift rates increase in 80Ma, when the intrusion occurs, increasing also the geothermal gradiente of the region and the relief. Comparing the rates its possible to conclude that the uplift is lower then the erosion rates, and the PC is the most stable since the intrusion where the relief is higher